Impacto de uma medicação sistêmica associada à aplicação tópica pós-operatória de um dessensibilizante na alteração de cor dentária promovida por peróxido de hidrogênio de alta concentração - Santos, Kaíza de Sousa (2020)
This study aimed to evaluate the effectiveness of dental bleaching in the office when pre- and postoperative systemic use of paracetamol/codeine (PACO) and postoperative application of topical desensitizer were made. This was a controlled, randomized, triple-blind, split-mouth clinical trial with 14 days of follow-up. Forty volunteers participated of this study. Half took the PACO medication and the other half a placebo (PLA) one hour before the bleaching procedure, and their hemiarchs were randomly assigned to receive a prophylactic paste (PAS) and Desensibilize Nano P™ (NP), generating four groups of therapeutic management by hemiarchs: G1 (PLA + PAS), G2 (PLA + NP), G3 (PACO + PAS) and G4 (PACO + NP) (n = 20). Two whitening sessions were performed on the entire sample with 35% hydrogen peroxide with two 20-minute applications, with an interval of one week between each session. Color evaluation was performed using the VITA Classical™ Scale and ShadeEye NCC™ Colorimeter. The statistical analysis was performed using the ANOVA 2-factor test with Tukey's post-test with the aid of the GraphPad Prism 8.0 software. The bleaching treatment with 35% hydrogen peroxide produced a change in color pattern after bleaching (P <0.005) and without statistically significant differences between therapeutic management (P> 0.005). Therefore, in-office tooth whitening using 35% hydrogen peroxide did not show any compromise in its clinical efficacy related to color after application of the tested desensitizing protocols.